Coulomb Stress Change of the 2004 Aceh Earthquake on Mount Sorik Marapi 2021 - Goldberd Harmuda Duva Sinaga; Martha Rianna Tambunan; Agoez Loeqman; Adhi Wibowo (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2021)
Sorik Marapi is an active volcanic mountain with an altitude of 2,145 meters located in Batang Gadis National Park, Sibanggor Julu Village, Mandailing Natal Regency, North Sumatra, Indonesia. Since the earthquake in Aceh on December 26, 2004, geological conditions in the western part of Sumatra Island have increased in stress. This affects the volcano in Sumatra, Mount Sorik Marapi, so it needs to be studied to find out the condition of changes in coulomb stress in Sorik Marapi. The method used in this study is a descriptive method with an analysis of the coulomb stress method. From the Aceh earthquake year of December 2004 to 2021, Mount Sorik Marapi experienced the highest average increase in coulomb stress in 2012, which was 0.171 bars. The highest average increase in shear in 2015 was 0.25 bars, and the highest average normal increase in 2018 was 0.202 bars. While at depth, Sorik Marapi mountain experienced an average change in coulomb stress highest of 0.368 bars, the average increase in the highest shear by 0.269 bars, and the average normal increase of 0.246 bars. All such increases are at a depth of 90 km below sea level. Based on the results of this study, it is stated that Mount Sorik Marapi experiences inconsistent changes in coulomb stress every year.